2022
DOI: 10.1007/s12633-021-01568-5
|View full text |Cite
|
Sign up to set email alerts
|

Metal Doping Silicates as Inorganic Ion Exchange Materials for Environmental Remediation

Abstract: Highlights Titano-silicate and in-situ dopped composites were prepared by precipitation technique. The capacity for Co(II), & Cd(II) ions sorbed on Co-TiSi, and Cd-TiSi is higher than obtained for TiSi by 1.81, and 1.41 values, respectively. Co-TiSi is suitable for the column technique for the removal of studied cations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The monolayer capacities (Q max ) of P(AA-AN)-talc for the sorption of Pb 2+ , Cd 2+ , Co 2+ , Zn 2+ , and Sr 2+ was compared with other sorbents reported in the literature. As represented in Table 8, the monolayer capacities of P(AA-AN)-talc toward the studied cations are higher than the previously reported values which suggested that P(AA-AN)-talc is a promising sorbent to remove Pb 2+ , Cd 2+ , Co 2+ , Zn 2+ , and Sr 2+ from aqueous solutions (Annadurai et al 2003;Anitha et al 2015;Ghasemi et al 2018;Abou-Lilah et al 2020;Hassan et al 2020;Herrera et al 2020;Abass et al 2021aAbass et al , 2022cKayranli 2021;Alsehli 2021;Abou-Mesalam et al 2022).…”
Section: Comparison Of Monolayer Capacity With Different Sorbents Rep...mentioning
confidence: 56%
“…The monolayer capacities (Q max ) of P(AA-AN)-talc for the sorption of Pb 2+ , Cd 2+ , Co 2+ , Zn 2+ , and Sr 2+ was compared with other sorbents reported in the literature. As represented in Table 8, the monolayer capacities of P(AA-AN)-talc toward the studied cations are higher than the previously reported values which suggested that P(AA-AN)-talc is a promising sorbent to remove Pb 2+ , Cd 2+ , Co 2+ , Zn 2+ , and Sr 2+ from aqueous solutions (Annadurai et al 2003;Anitha et al 2015;Ghasemi et al 2018;Abou-Lilah et al 2020;Hassan et al 2020;Herrera et al 2020;Abass et al 2021aAbass et al , 2022cKayranli 2021;Alsehli 2021;Abou-Mesalam et al 2022).…”
Section: Comparison Of Monolayer Capacity With Different Sorbents Rep...mentioning
confidence: 56%
“…These materials consist of tetrahedrons of the general formula MO 4 where M is Al or Si in natural zeolites. In the synthetic ones, M can stand for instance for Ti, Zr, B, or Ge [5][6][7][8][9]. Currently, the Structure Commission of the International Zeolite Association (IZA-SC) has recognized 247 unique types of zeolite network structures [10].…”
Section: Zeolitesmentioning
confidence: 99%